Data set: Institutionalisation and evolution of the Polish Eurolect and Polish Legislative Language - Biel, Łucja (RepOD, 2021)
Data set for the paper "From national to supranational institutionalisation: A microdiachronic study of the post-accession evolution of the Polish Eurolect", Perspectives (2022)The objective of this paper is to investigate the evolution of the Polish Eurolect, a supranational translator-mediated variety of legal Polish by: (1) analysing circumstances in which it emerged and took shape; and (2) tracking its development from the formative pre-accession to mature post-accession stage. The first part documents challenges faced at various stages of Eurolect formation, showing its growing institutionalisation as it shifts from the national to supranational level. Using corpus methods, the second part compares the formative stage of the Eurolect (1999-2003) to its mature stage (2011-2015) against the benchmark of the national legal variety. It demonstrates that Eurolects are dynamic and to some extent subject to controlled changes. The post-accession Eurolect is in principle better aligned with the national legal variety, especially for key genre markers (genre fidelity) and thanks to reduced translationese. It is also more formulaic and standardised. Nevertheless, the distance to national usage continues to be large for most patterns. A competing trend of the fossilisation of some over/underrepresented patterns was observed, contributing to the hybridity of the Eurolect. This is accompanied by the levelling out of translations: post-accession regulations and directions are more uniform in style and closer aligned with each other.